Effects of Advertising on Product Gender Perception: Washing Machines in the Turkish Market - Güngör, Oğuzhan; Tunç Cox, Ayça (Izmir Institute of Technology, 2016)
This thesis investigates the gender perception of washing machines through focusing on the advertisements that have feminine and masculine elements. In order to accomplish this, it examines the concept of gender via a thorough literature review. The Bem Sex Role Inventory (BSRI) that identifies the ones’ gender based on four categories including masculine, feminine, androgynous and undifferentiated is at the center of the study. Furthermore, the literature review includes an examination of the relationship between advertising and gender. Product gender perception too is studied in order to understand the elements that determine the gender of products. These elements are categorized in a systematic fashion to describe the gender of products. In light of the literature review, a two-phase experiment has been conducted. In the first phase, the gender of washing machines is investigated without any manipulations. Here Turkish version of BSRI is used to measure the gender of washing machines. Later, two different advertisements have been created based on the outcome of the literature review; one with feminine and one with masculine features. Participants in the first survey were randomly divided into two groups. In the second stage, participants were presented with stimulus. After that, participants’ perception of the gender of the washing machine has been tasted again. In light of the obtained data, it has been determined how advertisements containing feminine and masculine elements change the existing gender perception of a washing machine. Ultimately, this study demonstrated how the gender perception of a washing machine changes by the influence of advertisements.

Bu tez çamaşır makinesinin cinsiyet algısının feminen ve maskülen elementler içeren reklamlar vasıtasıyla değişimini incelemektedir. Çalışma öncelikle toplumsal cinsiyet kavramını içeren literatür taraması ile başlamıştır. Bununla beraber, toplumsal cinsiyetle ilgili kuramlar araştırılmış ve tartışılmıştır. Ayrıca kişilerin cinsiyet rollerini maskülen, feminen, androjen ve belirsiz olarak dört farklı kategoriye ayırarak inceleyen Bem Cinsiyet Rolü Envanteri hakkında bilgiler verilmiştir. Daha sonrasında literatür taraması reklamların toplumsal cinsiyet ile ilişkisi üzerine devam etmiştir. Literatür taraması, ürünlerin cinsiyet kazanımları üzerine devam etmiştir. Elde edilen bilgiler ışığında, ürünlerin hangi elementler vasıtasıyla cinsiyet kazandıkları kategorileştirilmiştir. Literatür taramasından elde edilen bilgiler ışığında bir araştırma hazırlanmıştır. Araştırma iki aşamada gerçekleşen bir deneyden oluşmaktadır. İlk aşamada katılımcılardan hiçbir dış faktör kullanılmadan çamaşır makinesinin cinsiyet rolünü ölçümlendirmeleri istenmiştir. Bu ölçümlendirmede Bem Cinsiyet Rolü Envanteri’nin Türk kültürüne uyarlanmış halinden yararlanılmıştır. Daha sonrasında literatür taramasından elde edilen bilgiler referans alınarak hazırlanmış feminen ve maskülen elementler içeren iki ayrı reklam hazırlanmştır. İlk ankete katılanlar rastgele iki gruba ayrılmıştır. Birinci gruba feminen elementler içeren reklam, ikinci gruba ise maskülen elementler içeren reklam gösterilmiştir. Katılımcılardan reklamlara bakarak tekrardan çamaşır makinesinin cinsiyet rolünü ölçümlendirmeleri istenmiştir. Elde edilen veriler ışığında feminen ve maskülen elementler içeren reklamların var olan çamaşır makinesi cinsiyet algısını ne şekilde değiştirdiği belirlenmiştir.
Ürün Cinsiyet Algısında Reklamın Etkileri: Türkiye Pazarında Çamaşır Makineleri
Thesis (Master)--Izmir Institute of Technology, Industrial Design, Izmir, 2016
Full text release delayed at author's request until 2019.01.23
Includes bibliographical references (leaves: 110-117)
Text in English; Abstract: Turkish and English
Keywords: Advertising and gender; Product gender perception; Washing machines; Gender